2014
DOI: 10.1007/s11356-014-3369-7
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial community toxic response to atrazine and its residues under atrazine and lead contamination

Abstract: Intensive use of atrazine and extensive dispersal of lead (Pb) have occurred in farmland with chemical agriculture development. However, the toxicological effect of their presence on soil microorganism remains unknown. The objective of this study was to investigate the impacts of atrazine or Pb on the soil microbiota, soil net nitrogen mineralization, and atrazine residues over a 28-day microcosm incubation. The Shannon-Wiener diversity index, typical microbe species, and a Neighbor-joining tree of typical spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 52 publications
1
18
0
2
Order By: Relevance
“…Our findings suggested a lack of correlation between pesticide persistence and soil microbial toxicity. This is in line with several previous studies which also did not observe any correspondence between pesticides persistence and the activity or abundance of AOMs (48)(49)(50)(51). The high response of potential nitrification to pesticide treatments, especially to EQ, together with the key role of this process in global N cycling forced us to further investigate the impact of pesticides on AOMs via molecular approaches.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings suggested a lack of correlation between pesticide persistence and soil microbial toxicity. This is in line with several previous studies which also did not observe any correspondence between pesticides persistence and the activity or abundance of AOMs (48)(49)(50)(51). The high response of potential nitrification to pesticide treatments, especially to EQ, together with the key role of this process in global N cycling forced us to further investigate the impact of pesticides on AOMs via molecular approaches.…”
Section: Discussionsupporting
confidence: 90%
“…A recent study reported that the concentration of ATR in groundwater has not decreased in some countries, even though ATR was banned > 20 years ago (Vonberg et al, 2014). Currently, studies on ecological toxicity (Chen et al, 2014(Chen et al, , 2015Kolekar et al, 2014;Papoulias et al, 2014) and environ- Fig. 6.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated repeatedly that heavy metals affect microorganisms in soils in various ways. They shift the structure of microbial populations, reduce their diversity, and affect the species composition, reproduction and activity of indigenous microorganisms (Wyszkowska et al 2013;Mikryukov et al 2015;Chen et al 2015). Some studies have focused on soil metal contamination and the effects on plants and microbes around mineral mining and smelting areas where high levels of metal pollution occur in soils and plants (Cui et al 2004;Kachenko et al 2006;Wang et al 2007a).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%